2019
DOI: 10.1080/15384101.2019.1689471
|View full text |Cite
|
Sign up to set email alerts
|

C-X-C chemokine receptor 2 correlates with unfavorable prognosis and facilitates malignant cell activities via activating JAK2/STAT3 pathway in non-small cell lung cancer

Abstract: Zhu (2019) C-X-C chemokine receptor 2 correlates with unfavorable prognosis and facilitates malignant cell activities via activating JAK2/STAT3 pathway in non-small cell lung cancer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…Targeting CXCR1/2 prevented JAK2 and STAT3 phosphorylation, consistent with the observations of Wei et al. ( 32 ). These findings are in line with our prior studies confirming that inhibition of CXCR2 signalling potentiated oxaliplatin-induced apoptosis in PC3 cells ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Targeting CXCR1/2 prevented JAK2 and STAT3 phosphorylation, consistent with the observations of Wei et al. ( 32 ). These findings are in line with our prior studies confirming that inhibition of CXCR2 signalling potentiated oxaliplatin-induced apoptosis in PC3 cells ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, inhibition of CXCR1/2 signalling in vitro did not modulate the magnitude of DNA foci formation or the rate of DNA repair in these cells. Recent research has confirmed that elevated CXCR2 expression can facilitate unfavourable prognosis and tumourigenesis via activation of the JAK2/STAT3 pathway ( 32 ). Our data suggest that radiation-induced CXCR1/2 signalling sustains the viability of PTEN -depleted cells using this exact mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the rabbit anti-p60 katanin antibody (Abcam, USA) at 1:20 dilution and goat anti-rabbit IgG H&L (HRP) (Abcam, USA) at 1:50,000 dilution were used as primary antibody and secondary antibody, respectively, in the IHC staining. All IHC procedures were performed as described in a previous study [13]. Finally, the expression of katanin P60 in tissue specimen was assessed by IHC score, which was obtained using a semi-quantitative scoring method as previously described [14].…”
Section: Ihc Stainingmentioning
confidence: 99%
“…Membrane-bound forms of chemokines allow communication with their receptors through direct cell-cell contact, which influences multiple fundamental biological processes and disease conditions, including cancer [ 77 ]. C-X-C chemokine receptor 2 ( CXCR2 ) is a key chemokine receptors that has been shown to promote NSCLC cell proliferation, invasion, and stemness while suppressing apoptosis and chemosensitivity, via activating JAK2/STAT3 signaling [ 78 ]. (3) The structural modeling showed that both GNG11 and chemokines in chemokine signaling pathway are not druggable, but GNG11 could form stable physical interactions with CXCR2 (DS = 0.834), CXCL3 (DS = 0.721), and PPBP (DS = 0.85) by a series of interfacial residues, which may offer more promising hotspots for drug targeting.…”
Section: Discussionmentioning
confidence: 99%